Positive Organizational Behavior (Sage Publications, 2007)
Positive Organizational Behavior is emerging as a truly contemporary movement within the classic discipline of Organizational Behavior. The best work of leading scholarrs is gathered together here. Chapters study the states, traits and processes that comprise Positive organizational behavior. In addition to mapping the field, this collection goes one step further and invites noted experts to identify the challenges facing positive organizational behavior.